2021
DOI: 10.3389/fcell.2021.760211
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tumor-Derived Exosome Programmed Death Ligand 1 on Tumor Immunity and Clinical Applications

Abstract: Programmed death ligand 1 (PD-L1) is a typical immune surface protein that binds to programmed cell death 1 (PD-1) on T cells through its extracellular domain. Subsequently, T cell activity is inhibited, and tumor immune tolerance is enhanced. Anti-PD-1/PD-L1 immune checkpoint therapy blocks the combination of PD-1/PD-L1 and rejuvenates depleted T cells, thereby inhibiting tumor growth. Exosomes are biologically active lipid bilayer nanovesicles secreted by various cell types, which mediate signal communicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…A study on oral squamous cell carcinoma (OSCC) revealed that macrophage polarisation toward the M2 subtype is promoted by programmed death ligand 1 (PD-L1) enriched exosomes derived from ER-stressed cancer cells. PD-L1 overexpression was linked to the poor overall survival of OSCC patients [ 205 , 206 ]. PD-L1 expression can also be enhanced in acidic TME [ 207 ].…”
Section: Exosomal Proteins In Cancer Progressionmentioning
confidence: 99%
“…A study on oral squamous cell carcinoma (OSCC) revealed that macrophage polarisation toward the M2 subtype is promoted by programmed death ligand 1 (PD-L1) enriched exosomes derived from ER-stressed cancer cells. PD-L1 overexpression was linked to the poor overall survival of OSCC patients [ 205 , 206 ]. PD-L1 expression can also be enhanced in acidic TME [ 207 ].…”
Section: Exosomal Proteins In Cancer Progressionmentioning
confidence: 99%
“…In addition to the induction of EMT, the molecules carried by TDsEVs can activate intracellular anti-apoptotic pathways [ 33 , 34 ] and induce drug efflux or sequestration [ 35 ]. Moreover, TDsEVs can also repress antitumour immune cell responses and induce immune suppressor cells [ 36 ].
Fig.
…”
Section: Antitumour and Protumour Effects Of Tumour-derived Small Ext...mentioning
confidence: 99%
“…Moreover, TDsEVs can also repress antitumour immune cell responses and induce immune suppressor cells [36].…”
Section: Tdsevs Promote Oncogenesis and Cancer Progression In The Tum...mentioning
confidence: 99%
“…Extracellular vesicles (EVs) are bilayer membrane-coated vesicles released by a variety of cells. Studies have demonstrated that the size and composition of EVs are heterogeneous and depend on the cellular source, state, and environmental conditions. ,, Accordingly, they can be classified into three types: (i) microvesicles that are formed by outward budding and fission of the plasma membrane; (ii) apoptotic bodies that are produced as blebs of cells undergoing apoptosis; and (iii) exosomes that are intraluminal vesicles (ILVs) contained in multivesicular bodies (MVBs) and released upon the fusion of MVBs with plasma membrane . Depending on the source of cells, EVs especially exosomes can be obtained using various laboratory isolation methods, such as ultracentrifugation, density gradient centrifugation, size exclusion chromatography, polymer-based precipitation, membrane filter, and immunoaffinity chromatography (Figure A), and harbor many different constituents, including a phospholipid bilayer membrane and membrane-associated proteins, as well as cytosolic components such as lipids, proteins, and RNAs (Figure B) .…”
Section: Introductionmentioning
confidence: 99%